On-the-job training, firm resources and unemployment risks: an analysis of the Swedish recession 1991-1993 - Carl le Grand (Institute for Labour Market Policy Evaluation (IFAU), 2000)
Two general questions are posed in this paper: (a) In what ways do characteristics of the firm where the worker is employed have an influence on the worker's risk to become unemployed? (b) How do general and specific skills acquired in the firm affect the worker's unemployment risk? The empirical analyses are based on three matched data sets: (i) survey data from the 1991 Swedish Level of Living Survey on individual and job related characteristics of the employees; (ii) register data on annual economic reports of private firms; and (iii) register data from the National Labor Market Board on registered unemployment. The main findings are: First, the resources and economic situation of the firm affect the workers' risks of becoming unemployed in several ways: The risks are larger for workers employed in small-scale firms, in labor intensive firms, in firms with small or negative profits, and/or in firms with a high debt to equity ratio. Moreover, these firm-level effects do not seem to be explained by the selection of productive, high capacity workers to resourceful, capital intensive and productive firms. Second, the effect on unemployment risks of the acquisition of skills within the firm is conditioned by the degree of transferability of such skills to other firms. A worker with skills that are firm specific will not be better off than a worker with relatively low job skills, while a worker with skills that can be of use with other employers has much less unemployment risks.
Keywords: J21; 330; Unemployment risks; firm